Heterogeneity in defining fetal corpus callosal pathology: systematic review. (9th June 2021) - Mahallati, H.; Sotiriadis, A.; Celestin, C.; Millischer, A. E.; Sonigo, P.; Grevent, D.; O'Gorman, N.; Bahi‐Buisson, N.; Attié‐Bitach, T.; Ville, Y.; Salomon, L. J.
ABSTRACT: Objective: Fetal anomalies of the corpus callosum (CC) have been reported in the prenatal imaging literature since 1985, and, especially when isolated, pose challenges for both the patient and fetal medicine specialist. The purpose of this study was to review systematically the literature on prenatally diagnosed abnormalities of the CC, focusing on the terminology used to describe abnormalities other than complete agenesis of the CC, and to assess the heterogeneity of the nomenclature and definitions used. Methods: This study was conducted in accordance with the PRISMA statement for reporting systematic reviews. A literature search was performed to identify prospective or retrospective case series or cohort studies, published in English, French, Italian, German or Spanish, reporting fetal imaging findings and describing anomalies of the CC. Quality and risk of bias of the studies were evaluated using the Newcastle–Ottawa scale and a modification of the scale developed by Conde‐Agudelo et al. for other fetal imaging studies. The data extracted included the number of patients, the number of different anomalies identified, the descriptive names of the anomalies, and, where applicable, the definitions of the anomalies, the number of cases of each type of anomaly and the biometric charts used. Secondary tests used to confirm the diagnosis, as well as the postnatal or post‐termination tests used to ascertain the diagnosis, were also recorded. Results: The search identified 998 records, and, after review of titles and abstracts and full review of 45 papers, 27 studies were included initially in the review, of which 24 were included in the final analysis. These 24 studies had a broad range of quality and risk of bias and represented 1135 cases of CC anomalies, of which 49% were complete agenesis and the remainder were described using the term partial agenesis or nine other terms, of which five had more than one definition. Conclusions: In comparison to the postnatal literature, in the prenatal literature there is much greater heterogeneity in the nomenclature and definition of CC anomalies other than complete agenesis. This heterogeneity and lack of standard definitions in the prenatal literature make it difficult to develop large multicenter pooled cohorts of patients who can be followed in order to develop a better understanding of the genetic associations and neurodevelopmental and psychological outcomes of patients with CC anomalies. As this information is important to improve counseling of these patients, a good first step towards this goal would be to develop a simpler categorization of prenatal CC anomalies that matches better the postnatal literature. © 2020 International Society of Ultrasound in Obstetrics and Gynecology